PENGAWASAN SEBAGAI INSTRUMEN PENEGAKAN HUKUM PADA PENGELOLAAN USAHA PERTAMBANGAN MINERAL DAN BATUBARA - Puluhulawa, Fenty U. (Jurnal Dinamika Hukum, 2011)
This research is intended to explain the monitoring as an instrument of law enforcement, to examine how the intensity of supervision on the business of mineral and coal, which is expected to support the establishment of law enforcement. The method in this study are socio juridical, with qualitative and quantitative methods. Research shows that in terms of planning and coordination of implementation supervision has not been implemented optimally, so that does not yet support the establishment of law enforcement. Based on this, it is necessary to the formation of an integrated environmental licensing system specialized in the management of the mining business.Keywords: monitoring, law enforcement, mining